Hubungan Status Gizi dengan DMF-T pada Murid SD Negeri 1 Piton Kecamatan Punung Kabupaten Pacitan - Zahra, Intan Maulia; Hidayati, Sri; Mahirawatie, Ida Chairanna (Jurnal Skala Kesehatan, 2020)
Abstract: The problem in this case study is the high index of DMF-T in Piton 1 Elementary School. The purpose of this study was to find the correlation of nutritional status with DMF-T among students in Piton 1 Elementary School. This type of research is analytic observational research with cross sectional approach. The population in this case study was Piton 1 Elementary Schools's students with a large sample of 60 students. The method used for data collection is the inspection method. The analysis technique used is the chi-square data analysis tehnique. The results showed that there was no relationship between nutritional status and DMF-T among students in Piton 1 Elementary School, Punung District, Pacitan Regency. Keyword : Nutritional Status, DMF-T, Body Mass Indez